In Spite of the Gods: The Strange Rise of Modern India - Edward Luce; LUCE (Edward) (Great Britain Littele Brown, 2006)
India is booming, poised to become one of the world's three largest economies in the next generation and to overtake China as the world's most populous country in 2032. Yet the subcontinent's spectacular growth is taking place against the backdrop of a society that has yet fully to come to terms with liberal modernity. Emerging India continues to be beset by deep contradictions: it is a fully fledged nuclear weapons state with almost 40 per cent of the world's malnourished children; a growing economic powerhouse with and enduring anti-materialist philosophy; it plays host t some of the world's most cutting-edge research and development, and yet is home to one of the most intolerant religious chauvinist movements in the world. In this groundbreaking book, which is scholarly and entertaining in equal measure, Edward Luce draws on his extensive personal experience of India to present a compelling snapshot of a country undergoing a remarkable transformation that will increasingly affect the rest of the world. We meet the people who are forging this very distinctive rising power: politicians, industrialists, activists and ordinary Indians of every caste. Luce moves beyond the surface anarchy and apparent contradictions of today's India to present an incisive but sympathetic perspective on an increasingly nationalistic democracy that will gradually rival China?and possibly the United States on the global stage over the coming decades. For all its complexity and many-layered histories, one thing is certain: India's fate matters. 'In Spite of the Gods is not only fun to read, it is also a deeply insightful account of contemporary India. Based on the author's rare combination of intimacy and detachment, the book can serve, remarkably enough, both as a fine introduction for unacquainted outsiders and as a mature scrutiny that is bound to stimulate insiders' ? Professor Amartya
Keywords: Indian History; Economic History; Social Conditions; Civilization